PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIS, AUDITORI, VISUAL, DAN INTELEKTUAL) TERHADAP PENINGKATAN KEMAMPUAN LITERASI NUMERASI SISWA DI SEKOLAH MENENGAH ATAS - Fatmawati, Alfi; Nuryadi (STKIP Subang, 2026)
The purpose of this study is to investigate whether or not the Somatic, Auditory, Visual, and Intellectual (SAVI) learning paradigm has an effect on the numeracy literacy of SMA Negeri 1 Sedayu's twelfth graders. Poor student numeracy abilities and the prevalence of traditional teaching techniques prompted the investigation. The non-equivalent control group design was used in this quantitative study as part of the quasi-experimental technique. We used SPSS's Independent Sample T-Test and N-Gain Score test to examine the data that our testing tools had produced. A Sig.(2-tailed) value of 0.005 < 0.05 was used to indicate a significant difference in improvement between the two groups in the findings. With an average N-Gain score of 0.52, the experimental group was considered to have